Effects of Different Land Status on Conservation Land and Income of Upland Rice Farming in Mausambi Village, Maurole Subdistrict, Ende Regency - Lanamana, Willybrordus; Fatima, Imaculata (Universitas Sebelas Maret, 2018)
The objectives of this study were to: (1) analyze the effects of different land tenure status on soil conservation level and (2) analyze the soil conservation level on production and income of upland rice farming. This research was conducted in Mausambi Village, Maurole Subdistrict, Ende Regency. Considerations in choosing a research village were seen from: a) the number of farmers who pawned agricultural land b) the extent of dry land and critical land c) the high percentage of poor farmers d) centers of food crop production and e) areas vulnerable to erosion. The population of upland rice farmers in Mausambi village was 214 people and consisted of 36 sharecroppers, 32 mortgagors and 146 owners. The method of sampling is cluster sampling, where this technique is a technique of selecting a sample from groups, small units or clusters. The sample size was calculated using Parrel formula. The sample size of land ownership status was 92 owners, 34 sharecroppers and 21 mortgagors. The analysis method used was multiple linear regression by including dummy variable of land tenure status and quantitative descriptive analysis. The result of the analysis shows that the farmers on land tenure status of owner are better in doing soil conservation efforts when compared to farmers on land tenure status of sharecropper and mortgagor. Owner dummy variable significantly affected the soil conservation level at 99% significant level. The positive sign means that the soil conservation level score on owner land tenure status is higher than the owner land tenure status of sharecropper and mortgagor. This is because in the owner farmers, the responsibility of soil conservation is higher than the farmers on other land tenure status. The well-done soil conservation efforts provide effect on the production and income of upland rice farming. The result of the research also shows that the land in the research site has not experienced severe erosion and soil conservation has been conducted but not maximized yet, especially on the aspect of contour farming, terrace treatment, terrace-strengthening plants, and tillage.